Prevalence and risk factors for RBC alloantibodies in blood donors in the Recipient Epidemiology and Donor Evaluation Study‐III (REDS‐III). Issue 1 (14th November 2018) - Karafin, Matthew S.; Tan, Sylvia; Tormey, Christopher A.; Spencer, Bryan R.; Hauser, Ronald G.; Norris, Philip J.; Roubinian, Nareg H.; Wu, Yanyun; Triulzi, Darrell J.; Kleinman, Steve; Gottschall, Jerome L.; Hendrickson, Jeanne E.
Abstract : BACKGROUND: Little information exists on red blood cell (RBC) alloimmunization in healthy US blood donors, despite the potential significance for donors themselves, blood recipients, and the blood center. STUDY DESIGN AND METHODS: Donor/donation data were sourced from the Recipient Epidemiology and Donor Evaluation Study‐III, which contains information from four US blood centers during 2012 through 2016. Multivariable logistic regression was used to assess prevalence of positive antibody screen by donor demographics, blood type, parity, and transfusion history. RESULTS: More than 2 million units were collected from 632, 378 donors, with 0.51% of donations antibody screen positive and 0.77% of donors having at least one positive antibody screen. The most common antibody specificities were D (26.4%), E (23.8%), and K (21.6%). Regression analysis indicated that increasing age, female sex, D‐negative status, and history of transfusion and pregnancy were positively associated with a positive antibody screen. Prior transfusion history was most strongly associated with a positive antibody screen, with donors reporting a prior transfusion having a higher adjusted odds ratio (3.9) of having a positive antibody screen compared to donors reporting prior pregnancy (adjusted odds ratio, 2.0). Though transfusion was a more potent immune stimulus for RBC alloantibody formation than pregnancy, the sheer number of previously pregnant donors contributed to pregnancy being a risk factor for the majority of clinically significant RBC alloantibodies detected in females. CONCLUSION: These findings on prevalence of and risk factors for RBC antibodies may have implications for future medical care of donors and for operations at blood centers.